Two New Labdane‐Type Diterpene Acids from the Wood of Cunninghamia konishii. Issue 1 (January 2015) - Chang, Chi‐I; Li, Yen‐Cheng; Yang, Chang‐Syan; Chao, Che‐Yi; Li, Yi‐Jen; Chang, Hsun‐Shuo; Huang, Ching‐Jeng; Kuo, Ching‐Chuan; Kuo, Yueh‐Hsiung
Abstract Two new labdane‐type diterpene acids, (12S)‐12‐hydroxylabda‐8(17), 13(16), 14‐trien‐18‐oic acid (1) and (12R)‐12‐hydroxy‐15, 16‐epoxylabda‐8(17), 13‐dien‐18‐oic acid (2), along with a known labdane‐type diterpene, (11E)‐15, 16‐bisnor‐13‐oxolabda‐8(17), 11‐dien‐19‐oic acid (3), were isolated from the MeOH extract of the wood of Cunninghamia konishii. Their structures were determined by analysis of spectroscopic data and comparison with the data of known analogs.